Medical teachers' perception towards simulation-based medical education: A multicenter study in Saudi Arabia. (25th March 2016) - Ahmed, Shabnam; Al-Mously, Najwa; Al-Senani, Fahmi; Zafar, Muhammad; Ahmed, Muhammad
Abstract: Objective: This study aims to evaluate the perception of medical teachers toward the integration of simulation-based medical education (SBME) in undergraduate curriculum and also identify contextual barriers faced by medical teachers. Methods: This cross-sectional observational study included medical teachers from three universities. A questionnaire was used to report teachers' perception. Results: SBME was perceived by medical teachers (basic sciences/clinical, respectively) as enjoyable (71.1%/75.4%), effective assessment tool to evaluate students' learning (60%/73.9%) and can improve learning outcome (88.8%/79.7%). Similarly, (91.1%/71%) of teachers think that simulation should be part of the curriculum and not stand alone one time activity. Teachers' training for SBME has created a significant difference in perception ( p  < 0.05). Lack of teachers' training, time, resources and the need to integrate in medical curriculum are major perceived barriers for effective SBME. Conclusion: Results highlight the positive perception and attitude of medical teachers toward the integration of SBME in undergraduate curriculum. Prior formal training of teachers created a different perception. Top perceived barriers for effective SBME include teachers' formal training supported with time and resources and the early integration into the curriculum. These critical challenges need to be addressed by medical schools in order to enhance the integration SBME in undergraduate curricula.